Jenis-Jenis Anura (Amphibia) Di Hutan Harapan, Jambi - Irvan Fadli Wanda; Wilson Novarino; Djong Hon Tjong (Jurnal Biologi Universitas Andalas, 2012)
An inventarisation of the Anuran species (Amphibia) at Harapan Rainforest, Jambi has been done from October 2011 to July 2012. We collected 127 samples from the field and made identification based on morphological characteristics. We identified 19 sepcies in which belong to five families i.e. Bufonidae (Phrynoidis asper Gravenhorst., Ingerophrynus parvus Boulenger., I. divergens Peters. and Pelophryne signata Boulenger.), Microhylidae (Kalophrynus pleurostigma Tschudi.), Dicroglossidae (Occidozyga sumatrana Peters., Fejervarya cancrivora Gravenhorst., F. limnocharis Boie., Limnonectes paramacrodon Boulenger., L. malesianus Kiew.), Ranidae (Hylarana erythraea Schlegel., H. parvaccola Peters., H. glandulosa Boulenger., H. nicobariensis Stolizka., H. baramica Boettger., H. siberu Mc.Cathy and Whitten., Odorana hosii Boulenger., Rana sp), Rhacoporidae (Polypedates leucomystac Boulenger.).Keywords: Amphibia, Anura, Identification key, Harapan Rainforest